MULTIPLE RESISTANCE OF Amaranthus palmeri TO ALS AND EPSPS INHIBITING HERBICIDES IN THE STATE OF MATO GROSSO, BRAZIL - NETTO,A. GONÇALVES (2016)
ABSTRACT This work was carried out in order to evaluate the susceptibility to ALS-inhibiting herbicides of the Brazilian biotype of glyphosate-resistant A. palmeri, considering different chemical groups. For that, four experiments were performed, each with one of the following herbicides: glyphosate, chlorimuron-ethyl, cloransulan-methyl and imazethapyr. In each trial, treatments were organized according to a 2x8 factorial scheme, in which two were the species of Amaranthus (A. palmeri and A. spinosus) and eight were the herbicide rates (16D, 8D, 4D, 2D, D, 1/2D, 1/4D and herbicide absence; being D the commercial rate of each product). For glyphosate, D = 720 g a.e. ha-1; for chlorimuron-ethyl, D = 20 g ha-1; for cloransulanmethyl, D = 30 g ha-1; for imazethapyr, D = 100 g ha-1. Glyphosate was not applied on A. spinosus. In all the trials, the Brazilian biotype of A. palmeri had low herbicide susceptibility, so it was possible to conclude this biotype has ALS-EPSPs multiple resistance. Therefore, considering only ALS-inhibiting herbicides, this population has sulfonilurea-triazolopirimidineimidazolinone cross-resistance.